Innovation strategy (2016)
This article presents the meanings of the corporate innovation strategy, as well as varied worldwide authors' proposals on realization and analysis of the strategy within enterprises. The current study aims to propose a new diagnostic tool for the innovation strategy within productive sector organizations. To achieve this purpose, scientific articles, PhD theses, technical documentation, and patents were revised. The databases consulted for this study were the following: Scopus, WIPO database the World Intellectual Property Organization, Japanese, German and European patents, and Google Scholar. In total, fortyfive documents were found. Subsequently, the most relevant variables of each document were identified, obtaining a total of 129 topics. Afterwards, two surveys were conducted and applied to the experts involved in innovation strategies in order to contextualize these variables, identify the main issues, necessities and opportunities, and prioritize the input, transformation process and output in regards to an innovation strategy. Concerning the most important results obtained from the issues, necessities and opportunities, the study highlights the insufficient knowledge on the formulation and implementation of the innovation strategies. Additionally, it underlines the lack of information about the innovative activity importance as a capability that can be developed systematically in the framework of an innovation strategy, concerning the input, transformation process and output. All issues had a high mode and a high consensus percentage above the group average, which denotes the importance of the innovation strategy formulation and implementation approach as well as the proposed topics for the diagnostics. Keywords: Innovation strategy, innovation strategy diagnostics, prioritization surveys